Parapluie / Hazwanie Iliana Hairul Hisham - Hairul Hisham, Hazwanie Iliana (2020)
Elle Cooperation produces a product which is called Parapluie. Parapluie is an umbrella which consist of additional features such as 3 wings solar fan, LED lights, switch button and USB port. The target market for this product is within the age 18-55. So mostly teenagers and adults. This product was sold in all 14 states of Malaysia due to the climate being hot and humid. To produce Parapluie, the company faced many challenges as in competitors. The competitors are Quanzhou Yixin Commerce & Trade Co., Ltd. and Shenzhen Moleey Umbrella Co., Ltd. Most of the competitor have their own advantages and ways to attract customer into buying their product.